2019
DOI: 10.1186/s42077-019-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of activated partial thromboplastin time versus antifactor Xa assay in monitoring continuous unfractionated heparin infusion therapy in obstetric intensive care unit

Abstract: Background: Unfractionated heparin (UFH) infusion therapy needs accurate tight control to prevent overanticoagulation that may result in hemorrhagic complications and also to prevent sub therapeutic level that may result in thrombotic complications. The aim of this study was to compare the most popular monitoring tool activated aPTT versus antifactor Xa to reach accurate monitor to UFH therapy in critically ill pregnant females. Results: Time to reach therapeutic level as well as total heparin dose required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although the number of institutions using anti-Xa for monitoring and dose titration is steadily increasing [ 34 ], studies comparing APTT-based protocols vs. anti-Xa-based protocols to monitor UFH infusion are scarce. Two comparative studies showed better therapeutic control when utilizing an anti-Xa protocol, considering earlier achievement of the therapeutic level and lower heparin dose requirement [ 35 , 36 ]. Another study suggested to use anti-Xa assays considering a lower accuracy for APTT to detect UFH underdosing and overdosing in critically ill patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of institutions using anti-Xa for monitoring and dose titration is steadily increasing [ 34 ], studies comparing APTT-based protocols vs. anti-Xa-based protocols to monitor UFH infusion are scarce. Two comparative studies showed better therapeutic control when utilizing an anti-Xa protocol, considering earlier achievement of the therapeutic level and lower heparin dose requirement [ 35 , 36 ]. Another study suggested to use anti-Xa assays considering a lower accuracy for APTT to detect UFH underdosing and overdosing in critically ill patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%